Learning culture and feedback: an international study of medical athletes and musicians. Issue 7 (July 2014) - Watling, Christopher; Driessen, Erik; van der Vleuten, Cees P M; Lingard, Lorelei
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at 'discuss'